TOURISM AND SOCIAL JUSTICE: A “CAPABILITY APPROACH” PERSPECTIVE - MARIUS YOSEF SERAN; I Nengah Dasi Astawa (Sanjiwani: Jurnal Filsafat, 2025)
This study aimed to analyze the relationship between tourism and social justice based on the Capability Approach developed by Amartya Sen and Martha Nussbaum. The research employed an interpretive qualitative method, using data collection techniques such as literature review, document comparison, and case study analysis. Primary data sources consisted of key literature exploring the philosophical concepts of both thinkers, as well as works related to the philosophy of tourism. Secondary data sources included tourism-related data obtained from online sources. The results of the study indicate the existence of access and capabilities in tourism, along with opportunities and challenges, both in enhancing and limiting the capabilities of individuals and communities, particularly in relation to the natural environment, socio-cultural aspects, the economy, and human resources. Criticisms regarding the limitations of surveys and measurements also emerged from the analysis of documents and case studies. These critiques aim to guide tourism studies, from planning stages through to evaluation and oversight, toward employing holistic, comprehensive, and interdisciplinary measurement methods. Thus, it is hoped that universal values of tourism, such as inclusivity and sustainability, can be implemented in the development of the tourism sector.